Mathematics Learning: Model Teams Games Tournament in Grade IV SDN 108/II Perumnas - Liza Helmalia Putri; Randi Eka Putra; Sundahry Sundahry (CV. Master Literasi Indonesia, 2025)
This study aims to improve the mathematics learning process and outcomes of fourth-grade students at SD Negeri 108/II Perumnas through the implementation of the Team Games Tournament (TGT) learning model. The background of this study is based on low student engagement and learning outcomes that have not yet met the Learning Objective Achievement Criteria (KKTP), which is 75. The method used was Classroom Action Research (CAR), implemented in two cycles, with the stages of planning, implementation, observation, and reflection. Data were collected through observation sheets for the learning process and cognitive learning outcome tests. The results showed an improvement in student learning, as evidenced by the percentage of learning outcomes in cycle I, meeting 1, at 40.74%, meeting 2 at 51.85%, then increasing to 55.56% in cycle II, meeting 1, and 66.67% in meeting 2. Improvements were also evident in cognitive learning outcomes. While no students achieved the KKTP (competent mastery level) in the pre-cycle, 12 students (44.44%) achieved mastery in cycle 1, and this increased to 20 students (81.48%) in cycle II. Thus, the implementation of the TGT model has proven effective in improving both student mathematics learning processes and outcomes. This model is recommended as an innovative, fun, and competitive learning strategy that elementary school teachers can use to improve the quality of learning.